Use of Bypassing Agents and Risk of Thromboembolic Events in Patients with Haemophilia and Inhibitors - Bykov, Katsiaryna; Bohn, Rhonda L.; Ewenstein, Bruce M.; Seeger, John D.; Avorn, Jerry; Bateman, Brian T. (Thrombosis and Haemostasis, 2017)
Patients with haemophilia and inhibitors to factors VIII or IX require bypassing therapy. The primary safety concern of bypassing agents is thromboembolism; however, the incidence of thromboembolic adverse events (TAEs) in haemophilia patients with inhibitors remains poorly characterized. The aim of this study was to assess the incidence of TAEs following exposure to bypassing agents in patients with haemophilia. Using U.S. Medicaid database (2000–2010), we identified a cohort of 719 males (mean age: 10 years at cohort entry) with haemophilia A or B and use of either recombinant factor VIIa (rFVIIa) or activated prothrombin complex concentrate (aPCC). Patients were followed up until loss of insurance eligibility, end of study period, or the first occurrence of TAE. Exposure was assessed on as-treated basis, and outcomes were adjudicated through review of healthcare claims. During the observation of a total of 2,823 person-years (py; mean follow-up: 3.9 years), 22 TAEs were identified, leading to incidence rates of 4.2 events (95% confidence interval [CI]: 1.8–8.3) per 1,000 unexposed py; 15.4 events (95% CI: 6.7–30.3) per 1,000 aPCC-exposed py; 18.2 events (95% CI: 8.3–34.6) per 1,000 rFVIIa-exposed py; and 29.7 events (95% CI: 6.1–86.7) per 1,000 py of concomitant exposure to both agents. The results were consistent across sensitivity analyses. In conclusion, we found no difference in the rate of TAEs across agents, but the data are compatible with a possibly increased rate associated with a combination therapy, highlighting the need for continuing safety monitoring through prospective registries or observational data.
Keywords: disseminated intravascular coagulation; haemophilia; deep vein thrombosis; drug safety